If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2k + 8) + -1(3k + -7) = 0 Reorder the terms: -1(8 + 2k) + -1(3k + -7) = 0 (8 * -1 + 2k * -1) + -1(3k + -7) = 0 (-8 + -2k) + -1(3k + -7) = 0 Reorder the terms: -8 + -2k + -1(-7 + 3k) = 0 -8 + -2k + (-7 * -1 + 3k * -1) = 0 -8 + -2k + (7 + -3k) = 0 Reorder the terms: -8 + 7 + -2k + -3k = 0 Combine like terms: -8 + 7 = -1 -1 + -2k + -3k = 0 Combine like terms: -2k + -3k = -5k -1 + -5k = 0 Solving -1 + -5k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -5k = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -5k = 0 + 1 -5k = 0 + 1 Combine like terms: 0 + 1 = 1 -5k = 1 Divide each side by '-5'. k = -0.2 Simplifying k = -0.2
| (6-1)+(2x+5)=168 | | 275-y=50 | | 2c^2-5=3 | | .36X-.035Y=10 | | 6a-5+3a=4a-3 | | -4v/7=-24 | | 1/3x-1/4(x-2)=4x | | -9/5=3y | | .36X+.035Y=.10 | | 2(Z-38)=5(Z-59) | | 11/15-(-3/5) | | 3/4n=-24 | | -5/8v=10 | | x^2+9t+4=0 | | 36X/16+3.5Y/16=10 | | .6(15c+10)=12c-9 | | 25.6=y/8 | | 6/5x-1/11=-6 | | 1/7x+1/3y | | -3(x-8)-5=9*(x+2)+1 | | 7a-4+29=3a-2 | | 36X+3.5Y=10 | | -6(6-x)+6=12-8(x+2) | | 6/5x-1/11=6 | | 2/3/4/5 | | 7u=14/3 | | (6x+2)+2(3x-5)+(x+10)= | | 4/7x=56 | | 3x+3=7x-23 | | x+4/5=-1/6 | | 160-36X=3.5Y | | 1/z-1/5z-1/4z=20/z+1 |